Blockade of Extracellular ATP Effect by Oxidized ATP Effectively Mitigated Induced Mouse Experimental Autoimmune Uveitis (EAU). - Ronglan Zhao; Dongchun Liang; Deming Sun (PLoS ONE)
Various pathological conditions are accompanied by ATP release from the intracellular to the extracellular compartment. Extracellular ATP (eATP) functions as a signaling molecule by activating purinergic P2 purine receptors. The key P2 receptor involved in inflammation was identified as P2X7R. Recent studies have shown that P2X7R signaling is required to trigger the Th1/Th17 immune response, and oxidized ATP (oxATP) effectively blocks P2X7R activation. In this study we investigated the effect of oxATP on mouse experimental autoimmune uveitis (EAU). Our results demonstrated that induced EAU in B6 mice was almost completely abolished by the administration of small doses of oxATP, and the Th17 response, but not the Th1 response, was significantly weakened in the treated mice. Mechanistic studies showed that the therapeutic effects involve the functional change of a number of immune cells, including dendritic cells (DCs), T cells, and regulatory T cells. OxATP not only directly inhibits the T cell response; it also suppresses T cell activation by altering the function of DCs and Foxp3+ T cell. Our results demonstrated that inhibition of P2X7R activation effectively exempts excessive autoimmune inflammation, which may indicate a possible therapeutic use in the treatment of autoimmune diseases.